Law of the Sea and Coastal-Marine Management in Costa Rica - Murillo, Carlos (2005)
The  relationship  between  man  and  sea  has  existed throughout  history  and  it  has  acquired  a  particular relevance in the last years due to environmental problems and the international and state regulations about the sea  ad  the  coastal-marine  space.  These  regulations increased greatly with the adoption of the 1982 Sea Right Agreement, which made the countries along the rivers  acquire  some  compromise  and  responsibilities concerning marine resource protection. The first part of this article is a brief summary of the evolution of the sea right. Then it is followed by the Costa Rican participation and contribution to this topic. Later, the disposition of the coastal-marine relations—specially the Costa Rican one—as well as the obligations of the riverside states to apply norms that guarantee their area´s protection and conservation are analyzed. This way, it is possible to access the sustainable management of coastal areas in order to point out the important role of international cooperation and regional approach.